Coils, magnets, and rings : Michael Faraday's world - Veglahn, Nancy; Spollen, Christopher J. (New York : Coward, McCann & Geoghegan, 1976)
A biography of the English scientist who believed that one should never stop asking questions. His questions led him to discoveries concerning electricity.
Bibliography: p. [4].
Keywords: Faraday, Michael, -- 1791-1867 -- Juvenile literature; Faraday, Michael, -- 1791-1867.; Scientists